Instrumented physical model studies of the peat soil-engineering structure interaction - Mohd Razali, Siti Nooraiin (2013)
The engineering structures are mostly constructed directly in contact with the ground and the response between the soil and the structure is termed as soil-engineering structure interaction. To understand the interaction, physical modelling is considered as a prime method of study. This physical model study has been conducted on peat soils obtained from the Malaysian Agricultural Research and Development InstituteIntegrated Peat Research Station (MARDI-IPRS) in Pontian, Johor. Peat is considered as unsuitable soil for supporting foundations in its natural state due to the high moisture content (>100%), high compressibility (0.9-1.5) and low shear strength (5-20 kPa) values. Peat also contains high organic matter (>75%), large deformation, high compressibility and high magnitude and rates of creep. The objectives of this study are to identify the engineering characteristic of the peat, analyse the deformation behaviour in peat soil based on physical modelling, analyse using physical model the stress distribution beneath the structure in peat soil and to compare the peat behaviour with sand. The reason of comparing these two different types of soil was to obtain the significant difference in terms of the settlement, stress and failure pattern. This study also helps to acquire basic understanding of the behaviour of settlement and stress of peat soil when load is applied to it. The rectangular model and the square model were used in pre-model study (PMS) to identify suitable indicators and observed the deformation of the peat/sand after the loading process. Meanwhile, a plane strain model cm was used in plain strain study (PSS) with instrumentations (Displacement Transducers and Soil Pressure Gauge) to investigate and observed the settlement and stress on the peat/sand. Various static loads were applied at the surface and the interaction between peat soil and sand with the structure was recorded based on all the deformations and stresses at various positions and levels. The water level was maintained at a constant level that is at the surface of the soil to prevent any induce stress due to the seepage of water and to omit settlement due to the lowering of the water table. The observations showed that the settlement in peat was higher compared to the settlement in sand because of the properties of peat that highly compressible compared to sand. The deformation of sand corresponds to general bearing capacity failure and deformation in peat shows punching shear failure. However, the stress in the sand was higher than the stress in peat because of the presence of water that affects the value of stress in peat.